EDITORIAL - Comité Editorial, FII (2000)
The advancement of soft technologies or management is creating the revolution of quality and productivity. in Peru, and there are 17 institutions certified with ISO 9001, including SENATI seeking a quality level that exceeds the requirements of users ...